2000
DOI: 10.1038/sj.ijo.0801372
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between lipaemia and central adiposity in subjects with an atherogenic lipoprotein phenotype (ALP)

Abstract: OBJECTIVE: To investigate the associations between indices of adiposity and cardiovascular risk factors in individuals with an atherogenic lipoprotein phenotype (ALP). SUBJECTS: Fifty-®ve men, aged 34 ± 69 y, body mass index (BMI) 22 ± 35 kgam 2 , with an ALP lipid pro®le (triglycerides (TG) 1.5 ± 4.0 mmolal, HDL`l.l mmolal; %LDL-3 b 40% total LDL). DESIGN: Each participant provided a fasting blood sample and underwent an 8 h postprandial assessment and had anthropometric measurements taken. OUTCOME MEASURES: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
12
1
Order By: Relevance
“…15,18 Body fat accumulation, especially that in the abdominal region, was positively associated with hyperinsulinaemia and all surrogate measures of insulin resistance and negatively associated with measures of insulin sensitivity in both the Caucasian and Sikh men. These data support previous studies in Caucasian men 26,30,[39][40][41][42] and Asian Indian men. 8,10,38,43,44 The higher circulating insulin levels associated with greater fat accumulation appeared to have compensated for the loss of insulin sensitivity in the Sikh, as no significant associations between fasted glucose and measures of adiposity were observed.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…15,18 Body fat accumulation, especially that in the abdominal region, was positively associated with hyperinsulinaemia and all surrogate measures of insulin resistance and negatively associated with measures of insulin sensitivity in both the Caucasian and Sikh men. These data support previous studies in Caucasian men 26,30,[39][40][41][42] and Asian Indian men. 8,10,38,43,44 The higher circulating insulin levels associated with greater fat accumulation appeared to have compensated for the loss of insulin sensitivity in the Sikh, as no significant associations between fasted glucose and measures of adiposity were observed.…”
Section: Discussionsupporting
confidence: 83%
“…This supports findings from other groups on Caucasian subjects. 21,22,30,[45][46][47][48] However, it was observed that the Caucasian men in the present study had a significant positive associations between fasting glucose and BMI, waist and subscapular. Although the Sikh men had higher insulin resistance than the Caucasian men, they also presented with higher fasted insulin, which could have contributed to the lack of relationship between glucose and body fat distribution.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations